KEEFEKTIFAN MODEL SAVI TERHADAP MINAT DAN HASIL BELAJAR IPA SDN LAWATAN 01 KABUPATEN TEGAL - Tiyas, Devitasari; M, Fatimah (Indonesian Journal of Conservation, 2019)
One of the less maximal factors of science learning is that teachers are less innovative in packaging the learning so that students become passive and less interested in science learning. It can have the impact on low interest student learning and outcomes, so that innovative is need in science learning, one of them by applying Somatic Auditory Visualization Intellectually (SAVI) learning model. This study aims to determine the effectiveness of SAVI learning model on the science learning in grade V of SDN Lawatan 01 Tegal Regency. Experimental design used was Quasi Experimental in the form of nonequivalent control group design. The result of hypothesis testing of effectiveness to nature science learning interest showed that thitung > ttabel (8,272 > 2,074) and the result of learning showed that thitung > ttabel (8,325 > 2,074). It can be concluded that the implementation of SAVI learning model is effetive on the interest and learning outcomes of social science student of grade V on the subject of the characther of light.